Prognostic impact of acute decompensated heart failure in patients with heart failure with mildly reduced ejection fraction - Schmitt, Alexander; Schupp, Tobias; Reinhardt, Marielen; Abel, Noah; Lau, Felix; Forner, Jan; Ayoub, Mohamed; Mashayekhi, Kambis; Weiß, Christel; Akın, Ibrahim; Behnes, Michael (European heart journal - acute cardiovascular care, 2024)
This study sought to determine the prognostic impact of acute decompensated heart failure (ADHF) in patients with heart failure with mildly reduced ejection fraction (HFmrEF). ADHF is a major complication in patients with heart failure (HF). However, the prognostic impact of ADHF in patients with HFmrEF has not yet been clarified.Consecutive patients hospitalized with HFmrEF (i.e. left ventricular ejection fraction 41-49% and signs and/or symptoms of HF) were retrospectively included at one institution from 2016 to 2022. The prognosis of patients with ADHF was compared with those without (i.e. non-ADHF). The primary endpoint was long-term all-cause mortality. Secondary endpoints included in-hospital all-cause mortality and long-term HF-related re-hospitalization. Kaplan-Meier, multivariable Cox proportional regression, and propensity score matched analyses were performed for statistics. Long-term follow-up was set at 30 months. A total of 2184 patients with HFmrEF were included, ADHF was present in 22%. The primary endpoint was higher in ADHF compared to non-ADHF patients with HFmrEF [50% vs. 26%; hazard ratio (HR) = 2.269; 95% confidence interval (CI) 1.939-2.656; P = 0.001]. Accordingly, the secondary endpoint of long-term HF-related re-hospitalization was significantly higher (27% vs. 10%; HR = 3.250; 95% CI 2.565-4.118; P = 0.001). A history of previous ADHF before the index hospitalization was associated with higher rates of long-term HF-related re-hospitalization (42% vs. 23%; HR = 2.073; 95% CI 1.420-3.027; P = 0.001), but not with long-term all-cause mortality (P = 0.264).ADHF is a common finding in patients with HFmrEF associated with an adverse impact on long-term prognosis.